inGenius: a crash course on creativity. - Seelig, Tina
Spark a revolution.- Bring in the bees.- Build, build, build, jump!.- Are you paying attention?.- The table kingdom.- Think of coconuts.- Move the cat food.- Marshmallow on top.- Move fast-Break things.- In anything can go wrong, fix it!.- Inside out and outside in.